2023
DOI: 10.1186/s13287-023-03254-2
|View full text |Cite
|
Sign up to set email alerts
|

Flow-dependent shear stress affects the biological properties of pericyte-like cells isolated from human dental pulp

Abstract: Background Human dental pulp stem cells represent a mesenchymal stem cell niche localized in the perivascular area of dental pulp and are characterized by low immunogenicity and immunomodulatory/anti-inflammatory properties. Pericytes, mural cells surrounding the endothelium of small vessels, regulate numerous functions including vessel growth, stabilization and permeability. It is well established that pericytes have a tight cross talk with endothelial cells in neoangiogenesis and vessel stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…This study was carried out using commercial human dental pulp stem cells (hDPSCs; CTIbiotech, Meyzieu-Lyon, France) cultured according to previously established protocols [ 32 ]. After cell expansion, a MACS ® separation kit (Miltenyi Biotec S.r.l, Bologna, Italy) was used to obtain a homogenous hDPSCs population through an immune selection against the surface antigens STRO-1 and c-Kit [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was carried out using commercial human dental pulp stem cells (hDPSCs; CTIbiotech, Meyzieu-Lyon, France) cultured according to previously established protocols [ 32 ]. After cell expansion, a MACS ® separation kit (Miltenyi Biotec S.r.l, Bologna, Italy) was used to obtain a homogenous hDPSCs population through an immune selection against the surface antigens STRO-1 and c-Kit [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Peripheral blood mononuclear cells (PBMCs) were isolated from the fresh whole blood of healthy adult volunteers (n = 5) by using Histopaque ® (Sigma Aldrich, St. Louis, MO, USA) according to the manufacturer’s instructions and preactivated by adding anti-CD3 and the costimulatory anti-CD28 monoclonal antibodies (BD Biosciences, Franklin Lakes, NJ, USA) to the culture medium [ 32 ]. PBMCs, resting or preactivated, according to each experimental evaluation, were then seeded and cultured in 6-well plates (3.5 × 10 6 cell/well) in the presence of both SLA titanium and CERID disks in order to investigate the biological effects of both implants on PBMCs.…”
Section: Methodsmentioning
confidence: 99%
“…Nuclei were counterstained with 10 μg/mL Hoechst 33342 blue dye. Images were acquired with a Nikon A1 confocal laser scanning microscope …”
Section: Methodsmentioning
confidence: 99%
“…Images were acquired with a Nikon A1 confocal laser scanning microscope. 37 SEM Analysis of Neural Cell Morphology. For SEM evaluations, cells cultured on substrate at different time points were fixed in 4% glutaraldehyde in phosphate buffer (pH 7.4), postfixed in 2% osmium tetroxide, dehydrated in an ascending series of alcohols, and dried with hexamethyldisilazane.…”
Section: Analysis Of Neurite Orientation and Average Neuritementioning
confidence: 99%
“…Among different MSC types, human dental pulp stem cells (hDPSCs) have been demonstrated to display pericyte-like features, to own a wide differentiation potential in vitro and to contribute to regenerating processes and to the maintenance of tissue homeostasis through direct histointegration, immunomodulatory abilities, and promotion of neoangiogenesis ( Janebodin et al, 2013 ; Nuti et al, 2016 ; Martinez-Sarrà et al, 2017 ; Paganelli et al, 2021 ). Recently, our research group has demonstrated that hDPSCs are able to modulate the immune response by activating different pathways, i.e., PD1/PD-L1 and Fas/FasL, and that the surrounding microenvironment may affect their immunomodulatory/inflammatory phenotype ( Di Tinco et al, 2021 ; Bertani et al, 2023 ). However, little is known about the role of hDPSCs in fibrosis processes.…”
Section: Introductionmentioning
confidence: 99%